2022
DOI: 10.2174/0929867328666210922161913
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota and Autoimmune Diseases: A Charming Real World Together with Probiotics

Abstract: Background: The role of gut microbiota in human disease is fascinating for hundreds of researchers worldwide. Many works have highlighted that gut microbiota modulates the immune system, and that its disruption can trigger autoimmune and inflammatory immune-mediated diseases. Probiotics are able to positively modify microbiota composition. Objective: Aim of this review is to report the most important findings regarding the effects of probiotics administration in the most common autoimmune disease and infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 84 publications
0
19
0
Order By: Relevance
“…This means that, while obtaining their habitat and nourishment from the host, these microbes protect the host from other pathogens, preventing infections. In fact, their interaction with the epithelial surface works as a physical barrier, increasing the competition for nutrients, producing antimicrobial peptides, and modulating immune cell function both in a pro- and anti-inflammatory fashion [ 5 , 6 ]. The imbalance in the composition of the normal microbiota, under the effect of environmental factors, is defined as “dysbiosis”.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that, while obtaining their habitat and nourishment from the host, these microbes protect the host from other pathogens, preventing infections. In fact, their interaction with the epithelial surface works as a physical barrier, increasing the competition for nutrients, producing antimicrobial peptides, and modulating immune cell function both in a pro- and anti-inflammatory fashion [ 5 , 6 ]. The imbalance in the composition of the normal microbiota, under the effect of environmental factors, is defined as “dysbiosis”.…”
Section: Introductionmentioning
confidence: 99%
“…Lately, the growing interest of researchers in the microbiota has spread because of technological advances—such as new gene sequencing techniques—that have led to the identification of resident bacterial populations in almost all organs and systems of the body, even in those that were once considered sterile [ 8 ]. While clarifying the role of the microbiota in health and disease, scientists have starting questioning the possibility to intervene by correcting this dysbiosis with the many weapons we have at our disposal, such as probiotics and prebiotics, right up to the more invasive faecal microbiota transplantation [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many research studies have supported the concept that gut microbiota plays a key role in modulating immunity, weight gain or loss, energy homeostasis, and obesity-related disorders ( Piccioni et al, 2022 ). Likewise, gut microbiota and their metabolites are associated with various non-alcoholic fatty liver diseases (NAFLDs), inflammatory bowels diseases (IBDs), hepatocellular carcinoma, cardiovascular diseases (CVDs), alcoholic liver disease (ALD), chronic kidney diseases (CKDs), and cirrhosis ( Hsu et al, 2020 ; Jansen et al, 2021 ; Ryma et al, 2021 ; Wang et al, 2021 ; Zhou et al, 2021 ; Philips et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The composition of gut microbiota can be improved with probiotics. [15,16]. Moreover, studies have shown that probiotics and their metabolites have anti-obesity potential, and their addition to the diet could reduce body weight and fat pad mass in rats [17].…”
Section: Introductionmentioning
confidence: 99%